Thematic analysis of urban accessibility indicators in eight Asian-based neighbourhood sustainability assessment tools (NSATs): a foundational study towards the development of NSATs for Ningbo city - Osebor, Felix Ikworia (2020)
In view of the scourge from the rapid rates of urbanisation across cities, coupled with the growing threats of climate change, the central discourse for achieving sustainability focuses on the role of cities and the resultant impacts from the activities of its urban inhabitants. These discussions fundamentally align with the assertion that achieving sustainability is mostly tenable, when the constituent parts of a city’s built environment are sustainable. Furthermore, they affirm the value of individual and collective human activities as key to directing urban sustainability initiatives. Consequently, efforts at addressing sustainability issues within cities are increasingly channeled to the community, district or neighborhood scale; affirming them as the basic components of cities, and the level where human activities meets developmental initiatives. This neighborhood-focused approach to addressing sustainability issues within cities, led to the proliferation of Neighborhood Sustainability Assessment Tools (NSATs).